2006
DOI: 10.1007/s11802-006-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of suspended particles and enhancement techniques on ultraviolet disinfection of a secondary effluent

Abstract: The concentration of suspended solids in the secondary effluent often varies widely, leading to frequent adjustment of the UV dosage to meet the disinfection criterion. In addition, a desired disinfection rate is difficult to achieve sometimes. The authors studied the particle size distribution, contribution of particle-associated Fecal Coliform (F. C. ), and their influences on UV disinfection. A combined disinfection process (chlorination with a subsequent UV disinfection) was tested to improve the disinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…As TSS concentrations in the effluent increase with ow rates, one can assume that the fraction of E. coli attached to TSS is less efficiently removed in the primary settlers 36 and that the UV efficiency is reduced by the presence of the particles. 37,38 In our case, no decrease of WWMP EMCs was observed in the WWTP. Our measurements at the inuent and effluent of the WWTP indicate that these compounds are not removed by the advanced primary treatment in place (Fig.…”
Section: Implications For Cso Managementcontrasting
confidence: 46%
“…As TSS concentrations in the effluent increase with ow rates, one can assume that the fraction of E. coli attached to TSS is less efficiently removed in the primary settlers 36 and that the UV efficiency is reduced by the presence of the particles. 37,38 In our case, no decrease of WWMP EMCs was observed in the WWTP. Our measurements at the inuent and effluent of the WWTP indicate that these compounds are not removed by the advanced primary treatment in place (Fig.…”
Section: Implications For Cso Managementcontrasting
confidence: 46%
“…Several studies highlight the role of the concentration and size of the suspended solids in UV disinfection [25,26]. Particles provide shelter to microorganisms against UV by absorbing or reflecting the UV.…”
Section: Uv-c Irradiationmentioning
confidence: 99%
“…Particles larger than 20 microns were shown to be more important in shielding than smaller particles (Qualls et al, 1983 and1985). Later, Wang et al (2006) further demonstrated that for similar TSS concentrations in different effluent samples, the particle size distribution could be different as a function of varying treatment processes prior to disinfection. In this research, the influence of particles size was used to explain differences in disinfection efficiency between samples.…”
Section: Figure 3 -Impact Of Ballasted Flocculation On Uv Disinfectiomentioning
confidence: 99%